2010
DOI: 10.3109/00016349.2010.514324
|View full text |Cite
|
Sign up to set email alerts
|

Is there an increase of postpartum hemorrhage, and is severe hemorrhage associated with more frequent use of obstetric interventions?

Abstract: The incidence of severe postpartum hemorrhage increased, and this may be related to more frequent use of obstetric interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
103
5
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 24 publications
15
103
5
10
Order By: Relevance
“…Incidence of atonic PPH significantly increased across vaginal, instrumental, and caesarean deliveries, irrespective of induction status. Consistent with the literature, 5,16 we found that the incidence of atonic PPH was higher for emergency than elective caesarean deliveries. The frequency of women diagnosed with atonic PPH and blood transfusion increased over the 11-year period, signalling a rise in more severe atonic PPH cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Incidence of atonic PPH significantly increased across vaginal, instrumental, and caesarean deliveries, irrespective of induction status. Consistent with the literature, 5,16 we found that the incidence of atonic PPH was higher for emergency than elective caesarean deliveries. The frequency of women diagnosed with atonic PPH and blood transfusion increased over the 11-year period, signalling a rise in more severe atonic PPH cases.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, increases in the frequency of severe PPH cases have also been observed. 1,[4][5][6] These findings coupled with limited national-level data available on PPH incidence prompted the International Postpartum Haemorrhage Collaborative Group to recommend further research on PPH to establish global trends. 7 A recent population-based study of maternal morbidity in Ireland identified PPH as the second most common cause of maternal morbidity during hospitalisation for delivery, and further found that PPH diagnosis increased between 2005 and 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports indicate that the incidence of postpartum hemorrhage (PPH) is increasing worldwide [2][3][4][5][6][7][8][9][10][11][12][13]. The physical impact of MOH has been studied extensively [14]; however hardly any data are available on psychological consequences.…”
Section: Introductionmentioning
confidence: 99%
“…En relación a la paridad, encontramos mayores pérdidas sanguíneas en el grupo de nulíparas en comparación con mujeres multíparas 16,17 . Este hecho es relevante, ya que el perfil de mujeres con parto precipitado corresponde habitualmente a mujeres multíparas con gestaciones a término, por lo que se debería estrechar la vigilancia en el grupo de nulíparas ante la mayor probabilidad de sangrado excesivo postparto.…”
Section: Discussionunclassified